The effect of ageing on isoniazid pharmacokinetics and hepatotoxicity in Fischer 344 rats. (9th November 2015) - Mach, John; Huizer – Pajkos, Aniko; Mitchell, Sarah J.; McKenzie, Catriona; Phillips, Leo; Kane, Alice; Jones, Brett; de Cabo, Rafael; Cogger, Victoria; Le Couteur, David G.; Hilmer, Sarah N.
Abstract: Isoniazid is the first‐line treatment for tuberculosis; however, its use is limited by hepatotoxicity. Age‐related differences in isoniazid pharmacokinetics and hepatotoxicity are uncertain. We aimed to investigate these in young (3 ± 0 months, n = 26) and old (23.0 ± 0.2 months, n = 27) male Fischer 344 rats following a low‐ or high‐dose toxic regimen of isoniazid or vehicle (4 doses/day over 2 days; low: 100, 75, 75, 75 mg/kg; high: 150, 105, 105, 105 mg/kg i.p. every 3 h). Fifteen hours after the last dose, animals were euthanized and sera and livers were prepared for analysis. Isoniazid treatment increased serum hepatotoxicity markers (alanine and aspartate transaminase) in young animals but not in old animals, and only reached significance with the high dose in young animals. Isoniazid treatment caused a trend towards an increase in necrosis in young animals with both doses. In contrast, microvesicular steatosis was increased in old isoniazid‐treated animals, reaching significance only with the low dose (steatosis prevalence in old: vehicle 1/9, isoniazid 4/5; P < 0.05). Among isoniazid‐treated animals, concentrations of toxic intermediates acetylhydrazine and hydrazine were higher in old than young animals ( P < 0.05). With both doses, hepatic cytochrome P450 2E1 activity was higher in young animals compared with old ( P < 0.05). There were no other age effects seen on any of the other measured enzymes involved in isoniazid metabolism (N‐acetyl transferase, amidase, glutathione‐S‐transferase). These results show age‐related changes in isoniazid pharmacokinetics may contribute towards differential patterns of toxicity and confirm that standard hepatotoxicity markers do not detect isoniazid‐induced microvesicular steatosis.